Birthplace Diversity of the Workforce and Productivity Spill-overs in Firms - René Böheim; Thomas Horvath; Karin Mayr (Austrian Institute of Economic Research (WIFO), 2012)
We analyse the effect of workforce composition by birthplace in Austrian firms on workers' wages. In our model, each worker's productivity may depend on whether the co-workers are of the same or of a different birthplace and wages depend therefore both on the relative size of workers' groups as well as on the production structure of firms. We derive empirically testable hypotheses about the effect of co-worker birthplace on wages using a stylised model of intra-firm spill-overs across worker groups. We find evidence for complementarities between workers of different birthplace in line with our model that persist (but become smaller in size) after we control for observable productivity characteristics such as occupation and work experience.
Keywords: 330; Immigration; Labour force composition; Labour productivity; Einwanderung; Arbeitsproduktivität; Arbeitsmigranten; Arbeitsmarktsegmentation; Österreich